1988
DOI: 10.1620/tjem.156.157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of porcine follicular fluid on LH and FSH secretion in rats.

Abstract: Effect of Porcine Follicular Fluid on LH and FSH Secretion in Rats . Tohoku J. exp. Med., 1988, 156 (2), 157-163 -To investigate a mode and a site of action of inhibin on FSH and LH secretion , in vivo and in vitro effects of porcine follicular fluid (PFF) on FSH and LH secretion were studied in male rats . PFF administerd i.v. suppressed basal FSH levels for 1-8 hr , but did not alter LH levels. O n the contrary, PFF given either 1 or 6 hr in advance , suppressed LH-RH stimulated LH responses as well as LH-RH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…In accord with many previous reports [10][11][12][13][14] including ours [15], basal FSH secretion was increased by activin A and suppressed by inhibin A. No significant change was observed in 3 mRNA levels accompanying changes in FSH and LH secretion, though f subunit mRNA decreased to approximately half of the initial level when activin A was added, and a slight increase in a mRNA levels caused by both inhibin A and activin A. Bilezikjian et al [7] observed a significant decrease in activin f monomer and dimer production when activin A was added to rat anterior pituitary cells and proposed a local negative feedback by activin of its own production.…”
Section: Discussionsupporting
confidence: 93%
“…In accord with many previous reports [10][11][12][13][14] including ours [15], basal FSH secretion was increased by activin A and suppressed by inhibin A. No significant change was observed in 3 mRNA levels accompanying changes in FSH and LH secretion, though f subunit mRNA decreased to approximately half of the initial level when activin A was added, and a slight increase in a mRNA levels caused by both inhibin A and activin A. Bilezikjian et al [7] observed a significant decrease in activin f monomer and dimer production when activin A was added to rat anterior pituitary cells and proposed a local negative feedback by activin of its own production.…”
Section: Discussionsupporting
confidence: 93%